The Responsibility of Government for Compensating Arrestees and Convicts in the Time of Innocence and Release in the Kurdistan Region - Rdhwan Shareef Salih; Turan Kareem Rasul (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Humans are responsible for their acts and decisions as well as for their treatment of goods and people under their care. Therefore, whenever an unauthorized act is committed and causes damage to another person, responsibility will occur for that damage and as a result, the sufferer needs to be compensated. Responsibilities are varied and are regulated by several different laws. One of the laws that regulates a type of civil liability is the Compensating Arrestees and Convicts in the Time of Innocence and Release Law of the Kurdistan Region of Iraq No. (10) of 2010. This law was passed to compensate for damages suffered by arrestees or convicts as a result of a decision issued unfairly or without legal evidence by judges. But so far, the law is not as effective as necessary, and citizens do not have enough information on the content of the law. This study therefore seeks to provide a legal interpretation and analysis of the provisions of this law. The main purpose of this study is to answer some questions, the most importantly: According to the Compensating Arrestees and Convicts in the Time of Innocence and Release Law, who has the right to claim compensation, and what does the compensation include? Which body is special to judge the compensation lawsuit? And what are the procedures for litigating the lawsuit and appealing the decisions? The study, based on the analytical method, concluded that any arrestee or convict who has been damaged by special judicial parties, has the right to litigate a compensation lawsuit in front of a special committee of the Appeals Court and the government should compensate for the material and moral damages that will be decided.